Los Quijano de Yucatán: entre la tradición y la modernidad - Laura Machuca Gallegos (Caravelle)
In this work the goal is to draw the experience of a Yucatecan family, the Quijano, whose members reached enormous local power, developing in several areas such as the city of Merida, sub-delegations, Church, Military, among others. We follow their trajectories since the late eighteenth century to the first decades of the nineteenth century. We analyze the strategies and tactics used by this family, comprising 15 children, and establish their networks of sociability, to understand the different responses to the situations that had they lived.